Exploring The Dynamics Of Teacher Performance Through Multivariate Analysis - Juli Hartini; Sri Setyaningsih; Suhendra (International Journal of Technology and Education Research, 2026)
Teacher performance plays a crucial role in educational quality and school effectiveness and is influenced by both organizational and psychological factors. This study examines a multivariate model of teacher performance by analyzing the direct and indirect effects of transformational leadership, empowerment, trust, and achievement motivation among junior high school teachers in Bekasi City. A quantitative survey design was employed involving 177 teachers selected through multistage proportional random sampling from 19 schools. Data were collected using validated five-point Likert-scale instruments and analyzed using SEM-PLS, supported by SITOREM for indicator prioritization. The results show that transformational leadership (β = 0.351), empowerment (β = 0.195), trust (β = 0.271), and achievement motivation (β = 0.189) have significant positive effects on teacher performance. Leadership and empowerment also demonstrate indirect effects through trust and achievement motivation. The model explains a substantial proportion of variance in teacher performance. SITOREM analysis identifies work quantity and achievement orientation as priority areas for improvement, while work quality and teamwork should be maintained.